Association between family caregivers' primary care experience when they report as patients and their stress related to caregiving: A pilot cross‐sectional study - Gen Nakayama; Shoichi Masumoto; Junji Haruta; Tetsuhiro Maeno (Journal of General and Family Medicine, 2023)
Abstract Background Few studies have examined whether family caregivers' own primary care providers can affect caregiving‐specific well‐being, such as caregiver stress. In this pilot study, we explored whether primary care experiences when family caregivers report as patients were associated with the stress of caregiving. Methods We used cross‐sectional data from a survey conducted in Japan between November and December 2020. We recruited family caregivers aged 40–74 years who were caring for community‐dwelling adults with chronic conditions. We assessed primary care experience using the Japanese version of the Primary Care Assessment Tool Short Form (JPCAT‐SF) and caregiver stress using the Japanese short version of the Zarit Caregiver Burden Interview. Results In total, 406 family caregivers were included in the analysis. The mean JPCAT‐SF total score was 42.1 out of 100 points. The proportion of caregivers who had higher caregiver stress was 48.8%. After adjusting for possible confounders, the JPCAT‐SF score was found to be significantly associated with caregiver stress (lower stress = 0 vs. higher stress = 1; adjusted prevalence ratio per 1 SD increase in JPCAT‐SF score = 0.89; 95% CI 0.80–0.98). Among the subscales of the JPCAT‐SF, longitudinality, and comprehensiveness (services available) were associated with caregiver stress. Conclusions Better primary care experiences when family caregivers reported as patients were associated with lower caregiver stress. Longitudinality, which includes focusing attention on the individual as a whole person, and comprehensiveness in the context of building provider‐patient relationships that make consultation easier when needed, were associated with lower stress.